Releasing of micro-objects based on local stream generation by high speed motion of end-effector. (2016) - Kim, Eunhye; Kojima, Masaru; Kamiyama, Kazuto; Horade, Mitsuhiro; Mae, Yasushi; Arai, Tatsuo
In micro-manipulation, releasing of micro-objects is a challenging work due to the difficulty of controlling adhesion forces. To overcome the adhesion force and place micro-objects with high position accuracy, in this paper, local stream generated by high-speed motions of an end-effector is proposed. A compact parallel link creates 3D end-effector motion at high-speed without uncontrollable vibration, which means local stream can generate enough force in a 3D direction to separate micro-objects. Applying the local stream created by the right end-effector, micro-objects including 55 µm microbeads and NIH3T3 cells attached to the left end-effector were released. To verify the placing positions of the objects, we compared four motions, 1D motions (X- and Z-directions) and circular motions (clockwise and counterclockwise directions), by analysing the trajectory of the objects after separation. From these results of experiments, we concluded that the circular motion (CCW) detached micro-objects in the nearest position from the end-effector.